ESTRATÉGIAS DE RASTREAMENTO DE TOXOPLASMOSE CONGÊNITA E SUAS COMPLICAÇÕES NOS RECÉM-NASCIDOS: REVISÃO DE LITERATURA - SIMO, JOELLE ARIANE LIEUCHE (2023)
INTRODUCTION: Congenital toxoplasmosis is an intracellular infectious gestational disease, whose causal agent is the protozoan Toxoplasma gondii. A zoonosis that causes the most common infectious gestational disease in men. Often associated with severe consequences, where the mother infected during pregnancy passes on to transmit the transplacental parasite to her fetus that manifests the repercussions later. Transmission is direct mother-child, the severity of the disease is associated with the time of maternal contact with the parasite, gestational age at the time of infection and the evolution for your baby, thus having time for the appearance of symptoms after contact between the first month to one year of life. BACKGROUND: To identify all infants infected with congenital toxoplasmosis in the first outpatient consultation of the specialized pediatric infectology service. Maternal diagnosis with positive IGM serology, mothers reports not having received adequate guidance on carrying out laboratory, serological and complementary tests during pregnancy and failure in pregnant woman's propaedeutics, transmition, diagnosis, treatmente and prevention. OBJECTIVES: Mothers infected during pregnancy mostly came from rural areas, practically all of them report not having received detailed care, hygiene guidance, dietry care, preventive care during pregnancy, even after negative laboratory tests in the first or second trimester it was not explained that they would have a risk of contracts toxoplasmosis in the third trimester, so serology tests weren’t performed in the third trimester. Among many others leading to infants contamination. METHODOLOGY: Literatura review through study from ministry of health and educacional manuais, textbooks, articles with the aim of promoting appropriate propaedeutic and prenatal action and therapeutic adherence. Study carried out in Brasil, articules, manuais and textbooks during this período had limitação of linguagem português and english publication date 2018 to 2021. RESULTS: This project is a literature review using manuals from the Ministry of Health, manuals for high-risk pregnant women, manuals for newborn health, pediatric infectology books, Internet articles based Pubmed, scielo and lilacs to complement the reading objective to describe, analyze and comment with evidence on the importance of serology, know how to interpret each stage, guide women and try together to correct failures in the collection, the time, how it interprets and when it refers to risk cases in the pregnant woman's prenatal care that can cause severe consequences for the newborn, in adolescence and adult life. CONCLUSION: It is necessary in the face of the findings of a disease that is referred to as a rare disease but that we observe and notice that it is more recurrent than the known serious diseases and that has a high mortality rate when neglected. It reinforces the care of pregnant women during prenatal care, that is, ideally guiding through awareness campaigns and educational lectures at a health unit, the screening of women of childbearing age living in rural areas, encourages the importance of planned pregnancy through control of preconception tests and continuous monitoring of pregnant women during prenatal care.